Do outro lado do espelho: a reconfiguração da narrativa transmidiática nas mídias digitais a partir da série Alice - Mascarenhas, Alan Mangabeira (2013)
From orality to mediation, narratives are surrounded by reconfiguration. The popularization of the use of computers and their post-mass functions has enhanced the ways of telling stories, bringing a communication system apparently horizontal when stories are told in environments that elevate the status of spectator to interactor. In a convergence era, these stories leave behind the narrative in a single media and become counted in a transmedia system, creating a fictional and immersive universe for viewers to interact. On one side you can see behind the scenes, the other side is the public. In the middle, a mirror that blurs fact from fiction. This text intends to resume atheoretical discussionof empirical situations on the concept of transmedia instituted by Henry Jenkins between 2000 and 2011. This discussion appears relevant from the time that new aspects of the concept become popular, and especially while new objects bring strange situations to the phenomenon, such as the national series Alice, produced and aired by HBO Latin America. Alice brings the discussion to production transmedia in Brazil, but highlights a peculiarity: the characters do not only exist on television and in social networks (Orkut, Twitter, Facebook), but also began to inhabit the everyday, the urban space, going to events and creating situations that functioned as unfolding of the events of the episodes, bringing new aspects to the concept of transmedia that Max Giovagnolli (2011) shall call "urban actions”. We question the television as this “mirror”, within this new narrative system and communication functions, and try to understand what new in bringing viewers to the center of this media.